Key Plant, Key Pests: Chinese Elm (Ulmus parvifolia) - Juanita Popenoe; Caroline G Roper Warwick; Richard C Beeson, Jr. (EDIS)
This series of Key Plant, Key Pests publications are designed for Florida gardeners, horticulturalists and landscape professionals to help identify common pests associated with common Florida flora. This publication, the second in the Key Plant, Key Pests Series, helps identify the most common pests found on the Chinese Elm (Ulmus parvifolia). This publication provides information and general management recommendations for anthracnose or black elm spot, powdery mildew, trunk canker, borers, eriophyid mites and leaf beetles. https://edis.ifas.ufl.edu/ep559